2019
DOI: 10.1108/hff-11-2018-0625
|View full text |Cite
|
Sign up to set email alerts
|

Mesoscopic approach for simulating nanofluid flow and heat transfer in a finned multi-pipe heat exchanger

Abstract: Purpose The lattice Boltzmann method is used to simulate the nanofluid flow and heat transfer inside a finned multi-pipe heat exchanger. Design/methodology/approach The heat exchanger is filled with CuO-water nanofluid. The Koo–Kleinstreuer–Li (KKL) model is used to estimate the dynamic viscosity and considering the Brownian motion in the simulation. On the other hand, the influence of nanoparticles’ shapes on the heat transfer rate is considered, and the best efficient shape is selected to be used in the in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
7
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(7 citation statements)
references
References 43 publications
0
7
0
Order By: Relevance
“…They studied the effects of the Rayleigh number, fin length, oscillating amplitude, oscillating period, thermal conductivity ratio (fin to fluid) and the non-dimensional Young's modulus. Other research studies can be found in literature (Ghalambaz and Noghrehabadi, 2014; Ghalambaz et al , 2014a, 2014b, 2019; Noghrehabadi et al , 2012a, 2012b, 2012c, 2013a, 2013b, 2014; Mansour et al , 2016; Ahmed et al , 2013; EL-Kabeir et al , 2007; Rashad, 2008; Rashad et al , 2011, 2017a, 2017b; Gorla et al , 2011; Sivasankaran et al , 2016; Liu et al , 2019; Aly and Pop, 2019; Nasrin et al , 2019; Sreedevi et al , 2019; Hayat et al , 2015; Mohammed et al , 2012; Makinde (2013); Şenay et al , 2019; Prakash and Agrawal, 2016; Rajesh et al , 2017; Khamis et al , 2015; Alsabery et al , 2019; Vemula et al , 2016; Fornalik-Wajs et al , 2019; Sun and Pop, 2014; Malvandi et al , 2017; Thumma et al , 2017; Rawat et al , 2019; Venkateswarlu et al , 2019a, 2019b). In these research works, different nanofluid parameters and various numerical and experimental models were addressed.…”
Section: Introductionmentioning
confidence: 94%
“…They studied the effects of the Rayleigh number, fin length, oscillating amplitude, oscillating period, thermal conductivity ratio (fin to fluid) and the non-dimensional Young's modulus. Other research studies can be found in literature (Ghalambaz and Noghrehabadi, 2014; Ghalambaz et al , 2014a, 2014b, 2019; Noghrehabadi et al , 2012a, 2012b, 2012c, 2013a, 2013b, 2014; Mansour et al , 2016; Ahmed et al , 2013; EL-Kabeir et al , 2007; Rashad, 2008; Rashad et al , 2011, 2017a, 2017b; Gorla et al , 2011; Sivasankaran et al , 2016; Liu et al , 2019; Aly and Pop, 2019; Nasrin et al , 2019; Sreedevi et al , 2019; Hayat et al , 2015; Mohammed et al , 2012; Makinde (2013); Şenay et al , 2019; Prakash and Agrawal, 2016; Rajesh et al , 2017; Khamis et al , 2015; Alsabery et al , 2019; Vemula et al , 2016; Fornalik-Wajs et al , 2019; Sun and Pop, 2014; Malvandi et al , 2017; Thumma et al , 2017; Rawat et al , 2019; Venkateswarlu et al , 2019a, 2019b). In these research works, different nanofluid parameters and various numerical and experimental models were addressed.…”
Section: Introductionmentioning
confidence: 94%
“…In a multi-pipe heat exchanger, Liu et al (2019) simulated the natural convection heat transfer of nanofluid using the lattice Boltzmann method and obtained the optimal pipe arrangement using Nusselt number and entropy generation as target parameters. Khanlari et al (2020) experimentally studied the performance of counter and parallel flow concentric tube heat exchangers.…”
Section: Characteristicsmentioning
confidence: 99%
“…Tohidi et al (2014) numerically analyzed the influences of nanofluid on heat transfer in the C-shaped channel, obtained the conclusion that, the heat transfer performance was improved 4%–14% when the concentration of Al 2 O 3 -water nanofluid increased from 1% to 3%, and it was improved 4%–18% when the concentration of CuO-water nanofluid increased from 1% to 3%, without significantly increasing pressure drop. In a multi-pipe heat exchanger, Liu et al (2019) simulated the natural convection heat transfer of nanofluid using the lattice Boltzmann method and obtained the optimal pipe arrangement using Nusselt number and entropy generation as target parameters. Khanlari et al (2020) experimentally studied the performance of counter and parallel flow concentric tube heat exchangers.…”
Section: Introductionmentioning
confidence: 99%
“…Nanotechnology as a pioneer science nowadays attracts attention of many researchers and authors to its various applicants. For instance, food and agriculture, heat exchangers, solar cells, car radiators, electronics applications, transportation, cooling process in industry and nuclear reactors, human health, miniature technology and drug delivery (Sheikholeslami et al, 2014;Kashani et al, 2019;Dinarvand, 2019;Sheikholeslami et al, 2019;Liu et al, 2019;Kalyane et al, 2019;Aly and Pop, 2019;Hayat et al, 2015;Mohammed et al, 2012). The word "nanofluid" is nominated by Choi (1995).…”
Section: Introductionmentioning
confidence: 99%